Perspectives for projects using an ecosystem approach to human health:: action research for health and the environment protection (Sustainability in Debate, 2018)
Betancourt, Óscar.; Mertens, Frédéric; Parra, Manuel. Enfoques ecosistémicos en salud y ambiente: aportes teórico-metodológicos de una comunidad de práctica. Quito, Ecuador: Ediciones Abya-Yala, 2016. 295 p. Disponível em http://ecosad.org/phocadownloadpap/nuestros-articulos/libro_de_la_copeh-lac-capitulo-iv-ecosistemas-salud-humana.pdf.